Formação continuada e prática de coordenadores pedagógicos no Maranhão: em cena o programa nacional escola de gestores - DINIZ, Camila Castro (2018)
This study is linked to the research line “Educational Institutions, Curriculum, Training and Teaching” of the Post-Graduation Program in Education, of Universidade Federal do Maranhão. Its general objective is to analyze the continued formation developed in the Specialization Course in Pedagogical Coordination offered by UFMA and its repercussions on the pedagogical practice of the graduated coordinators. And its specific objectives are to discuss the historical, legal context and the role of the pedagogical coordinator in the school; to understand the relation theory and practice in the formation of the pedagogical coordinator and how this influences in its performance; to analyze the demands that orient the field of the continuous formation of pedagogical coordinators from the National Program of School of Managers and the concretization of this policy, through the Specialization Course in Pedagogical Coordination offered by UFMA. It is a qualitative research, based on the presuppositions of the Historical Materialism Dialectic that seeks the apprehension of the object in its historical, multiple and totality processuality in order to capture the movements, contradictions and perspectives of the transformation of reality. The research field involved 4 municipalities (São Luís, Rosário, Morros and Santa Inês) attended by the Specialization Course in Pedagogical Coordination in Maranhão, the participation of 6 pedagogical coordinators, 6 managers and 12 teachers, totaling 24 subjects surveyed, distributed in 6 participating schools. The instruments chosen for the data collection were documentary analysis, semi-structured interviews and non-participant observation. The theoretical framework consisted of the contributions of authors such as Bruyne (et al., 1991), Gamboa (2012), Kosik (1976), Domingues (2009), Salvador (2000), Franco and Nogueira (2014), Rivas (2007), Medeiros and Rosa (1987), Saviani (2010), Orsolon (2001), Tanuri (2000), Mendes and Rodrigues (2006), Martins (2010) among others. According to the analyzes, it was found that the training received by the Specialization Course in Pedagogical Coordination was positive with important contributions to the formation and practice of the graduates, despite some perceived contradictions. Among them, although there was an understanding of the coordinators researched about their real assignments at school, in their pedagogical practice, we noticed an intensification process of their work that has favored the lack of a greater awareness of these professionals as to their role. In this sense, the function of the pedagogical coordinator needs to be demarcated in the school and the broader goals of this professional training, the base of which is seated in a processing perspective of reality, perhaps only be achieved in the long term, facing a new social and educational project that seeks to break with the existing opposition between capital and labor, which is responsible for increasing the fragmentation of knowledge and the overload of work.